Assisting Vietnamese mango farmers to capture greater benefits through improved supply chain management - Nissen, Robert J.; George, Alan P.; Price, Samuel; Nguyen, Duc D.; Tran, Doan N.T.; Ta, Tam M.; Doan, Tien H.; Nguyen, Chau; Rankin, Marlo K.; Russell, Iean W. (2009)
In the developing countries, traditional supply chains for fresh produce are giving way to new supermarket-led supply chains. The rapid transformation in the fruit and vegetable sector is due to the meteoric rise of supermarkets, hypermarkets, superstores, neighborhood stores, convenience stores, and discount stores, which are impacting on smallholder farmers. This change is also impacting on both upstream and downstream market intermediaries through the demand for safe, high-quality produce that has been produced in a sustainable manner. Problems with procurement in traditional supply chains include few product standards, inconsistent supply, highly variable transaction costs, and limited market information. Supermarket are now setting new procurement practices and supply systems which focus on reducing costs and improving quality to enable them to sell at lower prices. This will allow them to win over consumers and to obtain a larger market share. However, the ability of smallholder farmers, collector agents, and wholesalers in the Mekong Delta to meet safe food levels and the quality demands of domestic and overseas supermarkets can only be obtained through improving their production and supply chain practices. The implementation of new production and post harvest practices and the modernization of these supply chains may preclude many smallholder farmers from participating. Smallholder farmers must develop risk minimization strategies, such as forming collaborative marketing groups, implementing new crop management and production systems, improving the packaging, and creating more efficient transport methods and handling practices to provide a safe, competitively priced, high-quality product. Understanding the supply chain and where to intervene are essential if farmers and all supply chain participants are to benefit. In this paper, we describe mango supply chains in the Mekong Delta, provide empirical data collected from surveys, and highlight improvements smallholder farmers have been making to achieve greater benefits.
Keywords: Mango industry; Mango farmers -- Vietnam